Manajemen Proyek Sistem Informasi Pendataan Penjualan Donat Kawan Mamak Berbasis Web Dengan Menggunakan Framework Laravel - Utama, Arya Dwi; Yahfizham, Yahfizham (Jurnal Sains, Teknologi & Komputer, 2024)
This research aims to develop a web-based information system for managing donut sales at Kawan Mamak, in response to the rapid growth of the culinary industry. Using the Software Development Life Cycle (SDLC) approach, this system is designed to meet users' needs in efficiently managing sales data. Analysis of requirements, design, implementation, testing, and maintenance are the main stages in the development of this system. A solid database relationship between customer, sales, and donut variant tables is created to enhance system integration and responsiveness. A cheerful and efficient interface design is expected to improve user experience and positively contribute to the development of information technology in the culinary sector. With a focus on integrated sales management, this system aims to enhance Kawan Mamak's competitiveness by providing effective solutions to optimize the donut sales data recording process.